Trauma Team Training: Multidisciplinary Training for Trauma Management - Demian Szyld; Sarah E. Peyre; Zara R. Cooper; Diane Miller; Yvonne Michaud; Ali S. Raja (Association of American Medical Colleges, 2011)
Abstract Introduction Effective health care delivery provided by trauma teams can be enhanced through teaching and training multidisciplinary team members the essential elements of crisis resource management (CRM). The authors originally implemented a trauma team exercise focused on the resident learners and supported the central elements of advanced trauma life support. In 2009 this program was put on hold and a needs assessment was conducted. As a result the curriculum was rewritten to focus on the entire team training and CRM principles. The materials presented and the simulation scenarios enclosed are to highlight and teach role clarity, effective communication, resource management and utilization, and global assessment. Methods This resource takes approximately 4 hours to complete with the first hour consisting of introductions, orientation to the simulations, and a review of the institution's trauma system. The remaining 3 hours are comprised of three simulation scenarios (i.e., a 70-year-old man who is injured in a single-car collision, a 20-year-old woman who is 32 weeks pregnant and sustains injuries following intimate partner violence, and a multiple-case scenario). This is followed by a debriefing and sharing of lessons learned. Results To date, seven teams with 34 learners have been trained with this module. Discussion This educational unit successfully brings together multidisciplinary teams consisting of emergency medicine and surgery residents, nurses, patient care assistants, and medical students, to learn about CRM.